1.Zredukuj. a) (3x-5)+(-6x+4)
b) (4x-7)-(12x-3)
c) 2x(3x-4y+2)
d) 3(a-b)-(2a+b+1)
e) (3x-2)(4x+3)-4-2x(3x-1)
2.Przedstaw w postaci iloczynu
a) 15a+30
b) 8ab(kwadrat) -4ab+6b
c) 2x(x+y)-3(x+y)
d) ab+ac+bd+dc e) 8ax+2bx-ay-by
3.Oblicz:
a) 3x+y(kwadrat) x=1/3 y= -1
b) x(kwadrat) -3x-4 x= -4
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
1)
a) = 3x - 5 - 6x + 4 = -3x - 1
b) = 4x - 7 - 12x + 3 = -8x - 4
c) = 6x^2 - 8xy + 4x
d) = 3a - 3b - 2a - b - 1 = a -4b - 1
e) = 12x^2 +9x -4x - 6 -4 -6x^2 +2x = 6x^2 +7x - 10
2)
a) = 15(a + 2)
b) = 2b(4ab - 2a + 3)
c) = (x + y)(2x - 3)
d) = a(b + c) + d(b + c) = (b + c)(a + d)
e) = 2x(4a + b) -y(a + b)
3)
a) = 3 * 1/3 + (-1)^2 = 1 + 1 = 2
b) = (-4)^2 - 3 * (-4) - 4 = 16 + 12 - 4 = 24
1.Zredukuj
a) (3x-5)+(-6x+4)= 3x-5-6x+4= -3x-1
b) (4x-7)-(12x-3)= 4x-7-12x+3=-8x-4
c) 2x(3x-4y+2)= 6xdo kwadratu - 8xy-4x
d) 3(a-b)-(2a+b+1)= 3a-3b-2a-b-1=a-4b-1
e) (3x-2)(4x+3)-4-2x(3x-1)= 12x do kwadratu +9x-8x-6-4-6xdo kwadratu+2x= 6x do kwadratu + 3x-10
2.Przedstaw w postaci iloczynu
a) 15a+30= 15(a+2)
b) 8ab(kwadrat) -4ab+6b= 2b(4ab-2a+3)
c) 2x(x+y)-3(x+y)= 2x2+2xy-3x-3y= x(2x+2y-3)-3y
d) ab+ac+bd+dc= b(a+d)+c(a+d)
e) 8ax+2bx-ay-by= a(8x-y)+b(2x-y)
3.Oblicz:
a) 3x+y(kwadrat) = 3*1/3+(-1)do kwadratu= 1+1=2
b) x(kwadrat) -3x-4 = (-4)kwadrat -3*(-4)-4= 16+12-4=24